Factors That Affect Service Quality, Price, and Facilities on Consumer Satisfaction (Case Study on Excellent Group Lamongan Tourism Buses) - Ali Makhmud; Muhamad Imam Syairozi; Abid Muhtarom (Sean Institute, 2024)
PT. Excellent Four Brothers Group is a company that provides Tourism Bus rental services in Lamongan Regency. This study aims to determine the factors that affect service quality, price, and facilities on consumer satisfaction on Excellent Group Lamongan tourism buses. The technique used is probolity sampling, which is a simple random number of 100 respondents using the slovin formula, the method in this study uses a quantitative method. The data used in this study are primary data and secondary data obtained from the results of filling out questionnaires and data from the management of PT. Excellent Four Brothers. The test tools used were validity test, reliability test, classical assumption test, multiple linear regression, determination coefficient, t-test and F test. From the results of data processing, a calculated value for service quality (X1) was obtained of 3.920 > 1.984 with a significant value of 0.000 < 0.05, price (X2) of 3.128 > 1.984 with a significant value of 0.002 < 0.05, and facility (X3) of 3.309 > 1.984 with a significant value of 0.001 < 0.05, which means that the quality of service, price, and facilities have a partial effect on consumer satisfaction. From the F test, a Fcal value of 13.777 > Ftable 2.70 with a significant level of 0.000 < 0.05, which means that the quality of service, price, and facilities simultaneously affect consumer satisfaction. Meanwhile, the result of multiple linear regression was obtained with the equation Y = 5.270 + 0.202X1 + 0.142X2 + 0.215X3 + e